Estimated pulse wave velocity is associated with all-cause and cardio-cerebrovascular disease mortality in stroke population: Results from NHANES (2003–2014) - Huang, Huoming; Bu, Xiancong; Pan, Huachun; Yang, Shumin; Cheng, Wenke; Shubhra, Quazi T. H.; Ma, Niya (Frontiers in Cardiovascular Medicine, 2023)
Background: Arterial stiffness is a significant determinant and evaluation of the stroke population's cardio-cerebrovascular disease and all-cause mortality risk. Estimated pulse wave velocity (ePWV) is a well-established indirect measure of arterial stiffness. We examined the association of ePWV with all-cause and cardio-cerebrovascular disease (CCD) mortality in the stroke population in a large sample of US adults. Methods: The study design was a prospective cohort study with data from the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2014, between the ages of 18–85 years, with follow-up through December 31, 2019. 1316 individuals with stroke among 58,759 participants were identified; ultimately, 879 stroke patients were included in the analysis. ePWV was calculated from a regression equation using age and mean blood pressure. Survey-weighted Cox regression models were used to assess the association between ePWV and all-cause and CCD mortality risk. Results: After fully adjusting for covariates, the high ePWV level group had a higher risk of all-cause mortality and CCD mortality compared to the low ePWV level group. With an increase in ePWV of 1 m/s, the risk of all-cause and CCD mortality increased by 44%-55% and 47% -72%, respectively. When ePWV was＜8.8 m/s, an increase in ePWV per 1m/s was associated with a 165% (HR 2.65, 95% CI: 1.26-5.58; P=0.01) increase in all-cause mortality risk; when ePWV was ≥ 8.8 m/s, an increase in ePWV per 1m/s was associated with a 38 %(95% CI: 1.17-1.63; P＜0.001) increase in all-cause mortality risk.When ePWV was ＜12.1 m/s, an increase in ePWV per 1m/s was associated with a 124% (HR 2.24, 95% CI: 1.46-3.43; P＜0.001) increase in CCD mortality risk; when ePWV was ≥ 12.1 m/s, an increase in ePWV per 1m/s was not associated with in CCD mortality risk. Conclusion: ePWV is an independent risk factor for all-cause and CCD mortality in stroke patients. Higher levels of ePWV are associated with higher all-cause mortality and CCD mortality in stroke patients.